UPAYA GURU BIMBINGAN DAN KONSELING MEMPERSIAPKAN PESERTA DIDIK DALAM MEMILIH SEKOLAH LANJUTAN DI SMP NEGERI KOTA PADANG (Universitas PGRI Sumatera Barat, 2015)
Unit secondary education has an important role in helping the success of the students in choosing a school . For the process of implementation of the service is focused on the field of personal development and learning of learners . This study aims to reveal , describe and analyze the efforts of BK teachers prepare students in select schools . This study included descriptive analysis with quantitative approach. 30 samples from 8 school teachers BK SMP Padang selected by purposive sampling technique . Instruments used the Likert scale model . Data were analyzed using simple statistical techniques (techniques percentage) . Based on the findings of this study concluded efforts BK teachers prepare students in select schools in the category enough . Thus the efforts of teachers needs to be improved BK BK service program and service implementation BK.